2017
DOI: 10.1177/2472555217706649
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Specific Inhibitors of Trypanosoma cruzi Malic Enzyme Isoforms by Target-Based HTS

Abstract: Trypanosoma cruzi is the causative agent of Chagas disease. The lack of an efficient and safe treatment supports the research into novel metabolic targets, with the malic enzyme (ME) representing one such potential candidate. T. cruzi expresses a cytosolic (TcMEc) and a mitochondrial (TcMEm) ME isoform, with these activities functioning to generate NADPH, a key source of reducing equivalents that drives a range of anabolic and protective processes. To identify specific inhibitors that target TcMEs, two indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 31 publications
0
28
0
1
Order By: Relevance
“…Silence of ME1 significantly suppressed tumor growth and induced elevated cell apoptosis. Importantly, a recent report has revealed a panel of small molecules that could inhibit activities of malic enzymes (17). However, further studies are needed to confirm the clinical benefit of these inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silence of ME1 significantly suppressed tumor growth and induced elevated cell apoptosis. Importantly, a recent report has revealed a panel of small molecules that could inhibit activities of malic enzymes (17). However, further studies are needed to confirm the clinical benefit of these inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…In human cells, malic enzymes are encoded by three homologous genes (15,16), including ME1, which is located in the cytoplasm and enzymic activities require NADP; malic enzyme 2 (ME2), which is located in the mitochondrion and enzymic activities require NAD; and ME3, which is located in the mitochondrion and enzymic activities require NADP. These enzymes are widely distributed in nature and have highly conserved sequences and similar structural topologies across different species, suggesting that they have important biological functions (17).…”
Section: Introductionmentioning
confidence: 99%
“…donovani activities reported for this compound, considering the global similarities of enzymes within CYP51 family [40, 41]. Although involved in other studies as part of the GSK CHAGAS Box [42], no further information is currently available from the evaluation of TCMDC-143620 against other molecular targets, except for our previous cruzipain study [24] where it was found to be inactive (~7,5% of cruzipain inhibition at 25 μM). A complete profile of the off-target activity of TCMDC-143620 would be critical for future optimization efforts in order to achieve a suitable M32 MCPs probe from this compound.…”
Section: Discussionmentioning
confidence: 99%
“…Ranzani et al [124] have screened 30,000 compounds using the two-independent HTS strategies on infected cells and identified specific inhibitors that target the T. cruzi malic enzyme (TcMEs), which have trypanocidal activity against the intracellular stage of this pathogen in vitro.…”
Section: Phenotypic Approachesmentioning
confidence: 99%